Financial Crisis as a Factor of Stress and Conflict among Asnaf Families in Perlis - Rose, Nurul Naimah; Ishak, Aida Shakila; Marzuki, Nur Hidayah (Asian Social Work Journal, 2025)
This study explores the impact of financial crisis on stress and conflict among asnaf families in Perlis. Using a qualitative approach, in-depth interviews were conducted with 10 families registered under asnaf assistance programs with Perlis religious council. The findings highlight how financial instability exacerbates psychological distress, generates inter-family conflicts, and affects coping strategies. Four main themes emerged; financial hardship and psychological stress, economic strain and family conflict, coping mechanisms and resilience and lack of financial aids. The study provides insights for policymakers to design targeted interventions for vulnerable families.